Breast Cancer Human Epidermal Growth Factor Receptor 2 mRNA Molecular Testing Compared to Immunohistochemistry with Correlation to Neoadjuvant Therapy Response - Behairy, Mahmoud; Gabal, Samia Mohamed; Negm, Mohamed Sherif (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Breast cancer is the most common cancer type among women worldwide. Human epidermal growth factor receptor 2 (HER-2) is amplified in 10–34% of breast carcinomas and offers a therapeutic option from HER2-targeted therapy. Hence, HER2 is tested routinely in all breast cancer patients using immunohistochemistry (IHC) and in situ hybridization. Yet, some pitfalls do exist due to tumoral heterogeneity, inter and intrapersonal variations. mRNA expression assays can provide an alternative method for accurately measuring HER-2 avoiding these limitations. AIM: Comparing results of mRNA gene expression analysis for HER2 with IHC results and correlating it with the therapy response. MATERIALS AND METHODS: One hundred breast cancer core biopsies were tested for HER-2 using IHC and the same blocks were sectioned and tested for mRNA gene expression for HER2 by the Xpert breast cancer STRAT4 device. RESULTS: Concordance rate between mRNA expression and IHC for HER-2 was 93% with Kappa measurement showing perfect agreement (κ = 0.81, 95% CI, p < 0.0005). CONCLUSION: The study reveals high concordance between HER2 measurement using IHC and mRNA analysis. Molecular testing can provide an effective standardized method for HER-2 measurement in breast cancer patients.